2017
DOI: 10.1159/000465513
|View full text |Cite
|
Sign up to set email alerts
|

Clearance of Sclerostin, Osteocalcin, Fibroblast Growth Factor 23, and Osteoprotegerin by Dialysis

Abstract: Introduction: Fibroblast growth factor (FGF23), sclerostin, osteocalcin, and osteoprotegerin are important factors that control mineral bone metabolism. End-stage renal disease is associated with the pronounced dysregulation of mineral bone metabolism; however, the impact and clearance of mineral bone metabolism factors during dialysis remain largely undescribed. Methods: In a cross-sectional study, 10 chronic hemodialysis patients were treated with hemodialysis for 8 h using a high-flux filter and a dialysate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…Sclerostin, which is known to be cleared by convective clearance 28 was lower in HDF compared to HD patients even at baseline (p = 0.02), but no change was seen over the 12 month followup in either cohort. There was no difference in CTX in either group at any time point.…”
Section: J O U R N a L P R E -P R O O F -7 -mentioning
confidence: 82%
See 1 more Smart Citation
“…Sclerostin, which is known to be cleared by convective clearance 28 was lower in HDF compared to HD patients even at baseline (p = 0.02), but no change was seen over the 12 month followup in either cohort. There was no difference in CTX in either group at any time point.…”
Section: J O U R N a L P R E -P R O O F -7 -mentioning
confidence: 82%
“…Comparable to previous studies, we showed ~25% lower FGF23 levels in HDF 29 , whereas levels increased by over 100% in HD children. As seen with the dialytic J o u r n a l P r e -p r o o f -11 -clearance of other LMM compounds such as FGF-23, IL-6 and TNF-α, although an early reduction in plasma concentrations is seen with convective clearance 24 , this is not sufficient to further reduce plasma concentrations in the long-term, perhaps as production of these compounds overwhelms the clearance capacity of thrice-weekly dialysis 28 . Although protective in early CKD, FGF23 is known to have several "off-target" effects, independent of changes in mineral metabolism, on cardiac myocytes 47 with an increased prevalence of left ventricular hypertrophy 48 and premature mortality in adults with all stages of CKD 49 , stressing the importance of reducing FGF23 levels by HDF.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the secondary analysis of the CONTRAST study also demonstrated an association between high sclerostin levels and a lower mortality risk. A study by Carlson et al found that the clearance of sclerostin during hemodialysis occurs at a lower rate but intradialytic plasma levels of substrates involved in bone metabolism including sclerostin remains largely unchanged (Carlson et al 2017). The role of sclerostin as the mediator between bone and vasculature in chronic disease -mineral bone disorder (CKD-MBD) remains a fascinating analytical and clinical area for future further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The off-target detrimental biological activity of FGF23 excess potentially starts early therefore it should be addressed from pre-dialysis CKD. In addition, FGF23 excess of which the levels can be extremely high in patients with end-stage renal disease, may be not easily removed by dialysis even by convection technique [ 96 , 97 ]. This supports the evidence of LVH progression in long-term hemodialysis patients [ 22 , 23 ].…”
Section: Cardiac Effects Of Middle Moleculesmentioning
confidence: 99%